Cervical cancer screening in low- and middle-income countries: reply - Geldsetzer, Pascal; Lemp, Julia M. (The journal of the American Medical Association, 2021)
In Reply We agree with Dr Cremer and colleagues that in countries with older surveys, our estimates do not reflect the impact of more recent programs that have conducted cervical cancer screening. Our study used the most recent nationally representative surveys for which we were able to access microdata. Given the relatively low frequency with which such surveys are carried out and the time required to do so, our estimates for each country are inevitably somewhat outdated. We have therefore highlighted in our article that readers should interpret our findings as pertaining to the year(s) of data collection of the survey in a given country, rather than the country’s lifetime prevalence of cervical cancer screening at the time the article was published.